1984
DOI: 10.1111/j.2042-7158.1984.tb04387.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of liposomes in the topical application of steroids

Abstract: The effect of topical application of the androgen 5 alpha-dihydrotestosterone (DHT), both encapsulated in liposomes and solved in acetone, has been evaluated using the female hamster flank organ as a model system. Systemic absorption of DHT was significant from the acetone solution, but negligible from the liposome system. The topical biological effect is, however, proportionally diminished when the liposome system is used. Under the experimental conditions used, the lited using the female hamster flank organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 6 publications
(3 reference statements)
1
8
0
Order By: Relevance
“…Similar findings were reported for progesterone and econazole delivered from liposomes with a similar lipid composition [20]. In contrast, the topical input of 5 -dihydrotestosterone from similar vesicles was inferior to that from an acetone solution containing the same drug concentration when assessed by monitoring the size of the flank organs of the female hamster [21]. This contradiction was attributed to four possible factors; first, the use of different steroids; second, the first group monitored delivery by measuring skin deposition whilst the later studies measured a biological effect; then, the studies used different animals and finally, the schemes of application were different.…”
Section: Localized Effectssupporting
confidence: 81%
“…Similar findings were reported for progesterone and econazole delivered from liposomes with a similar lipid composition [20]. In contrast, the topical input of 5 -dihydrotestosterone from similar vesicles was inferior to that from an acetone solution containing the same drug concentration when assessed by monitoring the size of the flank organs of the female hamster [21]. This contradiction was attributed to four possible factors; first, the use of different steroids; second, the first group monitored delivery by measuring skin deposition whilst the later studies measured a biological effect; then, the studies used different animals and finally, the schemes of application were different.…”
Section: Localized Effectssupporting
confidence: 81%
“…Similar findings were reported for progesterone and econazole delivered from liposomes with a lipid composition of DPPC and CH (2:1), applied to guinea-pigs and compared with conventional dosage forms (Mezei 1985). Topical input from similar nano-structures (DPPC, CH; 1.1:0.5) encapsulating 5-dihydrotestosterone was inferior to that from an acetone solution containing the same drug concentration with respect to increasing the size of the flank organs of the female hamster (Vermorken et al 1984). These results were considered contrary to Mezei & Gulasekharam's early findings and the authors attributed the discrepancy to four possible reasons: firstly, the use of different steroids; secondly, Mezei & Gulasekharam used skin deposition as a measure for activity whereas the Vermorken group depended on the biological effect; thirdly, the use of different animals; and finally, the schemes of application were different.…”
Section: Localizing Effectsmentioning
confidence: 96%
“…Mezei & Gulasekharam (1980, 1982 were the ®rst to report that liposomes loaded with triamcinolone acetonide facilitated a three-to ®vefold accumulation of drug within the epidermis and dermis. Vermorken et al (1984) found increased localization of steroids within skin when liposomal 5-a-dehydrogenase was topically applied to female hamsters. Lasch & Wohlrab (1986) showed that egg lecithinacholesterol liposomes facilitate the penetration of cortisol into human skin and suggested vesicular disintegration in the deeper strata of skin.…”
Section: Discussionmentioning
confidence: 88%